Hubungan Ketergantungan Emosi Dan Kesepian Pada Emerging Adulthood Yang Menjalani Pacaran Jarak Jauh - Fredella, Denisa; Diah Sosialita , Tiara (CV RIFAINSTITUT, 2023)
Emerging adulthood those who are dating long distance feel insecure in their relationship and result in decreased emotional closeness which impacts on the level of loneliness. This study aims to determine the relationship between emotional dependency and loneliness in emerging adulthood who are in a long-distance relationship. Emotional dependence is a persistent pattern of unmet emotional needs that are attempted to be satisfied in a way that is not adaptive to others. Loneliness occurs when emotional and social needs are not met. This study uses a quantitative approach to the survey method. Participants in this study consisted of 156 emerging adults aged 18-25 years who underwent long-distance courtship. The measuring instrument used was The University of California, Los Angeles Loneliness Scale Version 3 (UCLA Version 3) and Partner's Emotional Dependency Questionnaire. which has been adapted into Indonesian. Data analysis used the Pearson's product moment correlation test with the help of SPSS 27 for Mac. The results of the research data analysis showed that the correlation coefficient between emotional dependence and loneliness in emerging adulthood who underwent long-distance courtship was 0.226, with a significance level of 0.004 (p>0.05). These results indicate that there is a positive and significant relationship, which means that the higher the emotional dependency, the higher the loneliness of emerging adults who undergo long-distance courtship.